2010
DOI: 10.1111/j.1528-1167.2009.02400.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the antiepileptogenic effects of an early long‐term treatment with ethosuximide or levetiracetam in a genetic animal model of absence epilepsy

Abstract: SUMMARYPurpose: Epilepsy is a heterogeneous syndrome characterized by recurrent, spontaneous seizures; continuous medication is, therefore, necessary, even after the seizures have long been suppressed with antiepileptic drug (AED) treatments. The most disturbing issue is the inability of AEDs to provide a persistent cure, because these compounds generally suppress the occurrence of epileptic seizures without necessarily having antiepileptogenic properties. The aim of our experiments was to determine, in the WA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
57
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 63 publications
11
57
0
1
Order By: Relevance
“…In the WAG/Rij rat model of absence epilepsy, early prophylactic treatment with ethosuximide, levetiracetam, or zonisamide (but not carbamazepine) before the onset of spike-wave discharges in the EEG suppressed the development of such absence-like seizures [31][32][33], which was also subsequently observed in the GAERS model of absence epilepsy [34]. These findings suggest that models are available in which epileptogenesis can be controlled and that early treatment during development may provide a strategy for preventing genetic epilepsy in susceptible individuals.…”
Section: Studies With Aedsmentioning
confidence: 99%
“…In the WAG/Rij rat model of absence epilepsy, early prophylactic treatment with ethosuximide, levetiracetam, or zonisamide (but not carbamazepine) before the onset of spike-wave discharges in the EEG suppressed the development of such absence-like seizures [31][32][33], which was also subsequently observed in the GAERS model of absence epilepsy [34]. These findings suggest that models are available in which epileptogenesis can be controlled and that early treatment during development may provide a strategy for preventing genetic epilepsy in susceptible individuals.…”
Section: Studies With Aedsmentioning
confidence: 99%
“…Dosage was calculated on the basis of the knowledge that rats drink, on average, 10-12 ml/100 g/day; the volume drunk was also checked weekly [44]. Drug solutions were freshly prepared, replaced 2 or 3 times a week, and bottles were wrapped in silver foil to exclude light [45,46].…”
Section: Chronic and Sub-chronic Treatment Proceduresmentioning
confidence: 99%
“…The number, but not duration, of the SWDs was found to be markedly suppressed during 3 months of sequential recordings performed after termination of treatment, revealing an antiepileptogenic potential of ethosuximide. This observation has been reproduced in subsequent studies [17,31] and extended to another genetic animal model for human absence epilepsy-the GAERS rat [32]. Furthermore, ethosuximide also seems to prevent comorbid anxiety [32] and depression [31,33] in the genetic absence epilepsy models, based upon observations in the open field and the forced swim test, respectively.…”
Section: Ethosuximidementioning
confidence: 72%
“…This was first demonstrated in a strain of spontaneously epileptic rats from Kyoto University in which early long-term treatment with a therapeutically relevant dose of levetiracetam inhibited the developmental expression of tonic convulsions and SWDs associated with absence seizures [58]. Later studies in the WAG/Rij rats confirmed that early long-term treatment with a therapeutically relevant dose of levetiracetam inhibits the developmental expression of SWDs [17,33].…”
Section: Levetiracetammentioning
confidence: 75%
See 1 more Smart Citation